Crystal structure and surface relaxation in Cr2O3 with a transferable oxide interaction potential - Rowley, A; Wilson, M; Madden, P (IOP, 1999)
An extended ionic interaction model, originally devised for alkaline earth oxides, is transformed into a potential for Cr2O3 by scaling parameters in a well-defined way to allow for the changes in cation radius and charge and in ionic polarizability. The extended ionic model allows for the induction of dipoles and quadrupoles and for deformations in the ionic shape, as perceived through the short-range interionic repulsion. The transformed potential predicts corundum as the lowest energy crystal, as is observed experimentally: induced quadrupoles are confirmed as playing an important role in stabilizing this structure. The predicted unit cell parameters and ionic positions are in good agreement with experiment. The model is used to study the relaxation of two low index surfaces, (0001) and (011̄2). The (011̄2) is shown to be energetically favoured over the (0001), which is consistent with the experimental observation of it as a free surface. The relaxation of the (0001) surface is shown to be in excellent agreement with LEED observations and with ab initio studies, in which several layers of ions are allowed to fully relax.